Réponses

2014-03-27T23:46:21+01:00
Bonsoir,

A = (3x - 2)² - (4x + 1)²

1) Développer A.

A = (9x² - 12x + 4) - (16x² + 8x + 1)
   = 9x² - 12x + 4 - 16x² - 8x - 1
   = -7x² - 20x + 3

2) Factoriser A.

A = (3x - 2)² - (4x + 1)²
   = [(3x - 2) + (4x + 1][(3x - 2) - (4x + 1)]
   = (3x - 2 + 4x + 1)(3x - 2 - 4x - 1)
   = (7x - 1)(-x - 3)

3) Résoudre A = 0

(7x - 1)(-x - 3) = 0
7x - 1 = 0   ou  -x - 3 = 0
7x = 1   ou  -x = 3
x = 1/7   ou  x = -3

S = {1/7 ; -3}
2014-03-28T00:10:25+01:00

Soit A=(3x-2)²-(4x+1)²


développer A

A = (9x² - 12 x + 4) - ( 16x² +8x +1)

A = - 7x² - 20x + 3


factoriser A

A = (3x-2-4x-1) (3x-2+4x +1)

A = ( -x -3) ( 7x-1)

vérification : ( - x-3) ( 7x-1) = -7x² +x - 21x +3 = -7x² -20x +3

résoudre pour A =0

 (-x -3) (7x -1) = 0

-x -3 = 0    ou    7x-1 = 0

x   =  -3      ou          x = 1/7

l'équation admet deux solutions : (-3 ; 1/7)